Occupational repercussions of companions of children in hospitalization situations: experience report in multiprofessional residence (Research, Society and Development, 2022)
During hospitalization, the child is the main target of the repercussions of this process, however, in addition to the reverberations and damages that this can cause the child, the family and especially those who perform the role of companion are also directly affected. This is a descriptive, qualitative professional experience report, with the aim of describing the occupational repercussions of caregivers of children in a state of hospitalization, in addition to the performance of Occupational Therapy. Care was carried out with the companions of children in a situation of hospitalization with various objectives, such as minimizing the effects arising from the hospitalization process, stimulating occupational balance and promoting better occupational performance, (re)signifying the hospitalization process and among others. In short, it was possible to understand what occupational repercussions the hospitalization process can cause for the companion and what is the importance of assistance for this public within this context, especially regarding the work of the Occupational Therapist.